The impact of mouth breathing on dentofacial development: A concise review - Lin, Lizhuo; Zhao, Tingting; Qin, Danchen; Hua, Fang; He, Hong (Frontiers in Public Health, 2022)
Mouth breathing is one of the most common deleterious oral habits in children. It often results from upper airway obstruction, making the air enter completely or partially through oral cavity. In addition to nasal obstruction caused by various kinds of nasal diseases, the pathological hypertrophy of adenoids and/or tonsils is often the main etiologic factor of mouth breathing in children. Uncorrected mouth breathing can result in abnormal dental and maxillofacial development and affect the health of dentofacial system. Mouth breathers may present various types of growth patterns and malocclusion, depending on the exact etiology of mouth breathing. Furthermore, breathing through the oral cavity can negatively affect oral health, increasing the risk of caries and periodontal diseases. This review aims to provide a summary of recent publications with regard to the impact of mouth breathing on dentofacial development, describe their consistencies and differences, and briefly discuss potential reasons behind inconsistent findings.